2021
DOI: 10.3390/electronics10030313
|View full text |Cite
|
Sign up to set email alerts
|

Portable DC Supply Based on SiC Power Devices for High-Voltage Marx Generator

Abstract: The paper describes major issues related to the design of a portable SiC-based DC supply developed for evaluation of a high-voltage Marx generator. This generator is developed to be a part of an electromagnetic cannon providing very high voltage and current pulses aiming at the destruction of electronics equipment in a specific area. The portable DC supply offers a very high voltage gain: input voltage is 24 V, while the generator requires supply voltages up to 50 kV. Thus, the system contains two stages desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…The component on the primary side is replaced by a sinusoidal current source, and the input voltage on the secondary side is expressed as a square wave component. In addition, the of 13 average value of the sinusoidal current is the output current, expressed by Equation (6). Equation ( 7) represents the voltage across the secondary transformer.…”
Section: Analysis Of Equivalent Circuit Of the Proposed Parallel Resonant Convertermentioning
confidence: 99%
See 1 more Smart Citation
“…The component on the primary side is replaced by a sinusoidal current source, and the input voltage on the secondary side is expressed as a square wave component. In addition, the of 13 average value of the sinusoidal current is the output current, expressed by Equation (6). Equation ( 7) represents the voltage across the secondary transformer.…”
Section: Analysis Of Equivalent Circuit Of the Proposed Parallel Resonant Convertermentioning
confidence: 99%
“…However, such a high-voltage power supply has problems, such as a decrease in reliability owing to an increase in output ripple voltage and a decrease in power density owing to an increase in volume. Consequently, several studies have been conducted in order to reduce the output voltage ripple or improve the power density and to ensure the miniaturization, high efficiency, and reliability of high-voltage DC power supplies [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, high-frequency transformer-based converters are most commonly used. A literature review performed in the area of high-voltage power supplies for rapid capacitor charging showed that in most cases, topologies with full-bridge converters are used [12][13][14][15][16][17][18][19] due to the versatility of this topology and the possibility of implementing various control algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the external DC power supply is integrated into the designed high-voltage power supply. Most plasma power supplies are based on stand-alone DC power combined with highvoltage power supplies [14,15] or Marx generators [16,17], and are thus bulky and heavy, with limited portability. To overcome these disadvantages, in this study, a flyback PFC converter [14,18] is use to replace the front-end DC power supply.…”
Section: Introductionmentioning
confidence: 99%